Uso de la Inteligencia Artificial en la enseñanza de Matemática en el nivel de educación secundaria - González Jiménez, Pablo Fernando (2024)
Artificial intelligence has the potential to become a valuable tool for teaching. The present research aims to analyze the use of artificial intelligence in the teaching of Mathematics at the secondary school level. In order to carry out this work, a systematic documentary study was conducted with an exploratory-descriptive scope, on which was theoretically based the research objects. In addition, the information from 48 literary sources where the application of intelligent systems to teach the mentioned subject was evaluated. The results showed that the most used AI in education is intelligent tutors; they also revealed that the main aspect to consider for the implementation of these systems is technical and technological resources and that the insertion of AI in education does not follow a single methodological process, but it is coupled to different phases of these. Finally, it was concluded that intelligent systems improve learning efficiency by providing options to automate and personalize teaching. Keywords: Artificial Intelligence, Mathematics teaching, Secondary education, Didactic guide.